Pengembangan Ontologi Semantik Pada Domain Produk Kosmetik (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
The circulation of hundreds to thousands of cosmetic products in the world causes more considerations to be had in choosing the right cosmetic products. The number of cosmetics products available with various types and criteria requires buyers to be more careful in determining the right cosmetic products. The right solution to overcome these problems is to use the concept of semantic ontologi. The ontologi development method used is Methontologi. This method is one method of building an ontologi model that can be reused for an ontologi that is built for further research. The cosmetic products ontologi development model produces 3 classes, 5 object properties, 4 data properties, and 62 individuals or instances in each class. The ontologi evaluation process by performing SPARQL queries also gives appropriate results. Keywords: Ontologi, Cosmetic, Methontologi, Query SPARQL, ProtÃ©gÃ©